PROSES PENGISIAN STOPE DENGAN MATERIAL TAILING DI PERTAMBANGAN EMAS PONGKOR - Oktaviani, Revia (APLIKA Jurnal Ilmu Pengetahuan dan Teknologi, 2008)
Underground mine system applied in mining of gold Pongkor is cut and fill in overhand stoping. Every advances from mining activity must be followed with recharging stope at district ex-production. This impregnation meant as buffer and base treads on the workers when continuing activity of other production. To cost effective supply of material and exploits material is around in mine. Hence applied tailing result of processing as the filler material. Problems arising is if target of produce of 500 ton/day, hence tailing material insufficient hole plug to ex the production. Result of analysis happened transformation of density ore out of 265 ton/m3 becomes 1952 ton/m3 so that acquired percent become 73.3%. Because percentage tailing required is 94%, then happened lacking of filler material 108.48 m3/day. To overcome it need to be strived acquired percent langer ones by minimizing leakances happened at stone and can apply trass material which many there is around location